SEJARAH KESULTANAN RIAU-LINGGA PADA MASA PEMERINTAHAN SULTAN MAHMUD RIAYATSYAH 1777-1812 - Akbar, Nuzu Chairu; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: The Riau-Lingga Sultanate is a Malay-patterned kingdom that is under the Malay Peninsula. The Riau-Lingga Sultanate was the successor of the Malacca Sultanate which became the beginning of the founding of Malay Empire with the famous sultan, Sultan Mahmud Riayatsyah who ruled from 1777-1812. Sultan Mahmud Riayatsyah's government began in 1777. The purpose of this study was (1) To know the government of the Riau-Lingga Sultanate during the leadership of Sultan Mahmud Riayatsyah (2) To know out the social, political and economic conditions of the Riau-Lingga Sultanate during the reign of Sultan Mahmud Riayatsyah (3) to know the business carried out by Sultan Mahmud Riayatsyah in strengthening the position of the sultanate during his reign in the Sultanate of Riau-Lingga (4) to know the distribution of power at the end of Sultan Mahmud Riayatsyah's administration. This research uses historical methods. The results of this study are that the reign of Sultan Mahmud Riayatsyah was the starting point for the development of the cities of Tanjungpinang and Daik Lingga as a bustling city. Defense cooperation with outside parties is well established in strengthening its position. Advanced economic development through trade, gambier plantations and tin mining at that time. Islam developed rapidly at that time with the establishment of the Sultan Lingga Mosque in Daik Lingga. The period of his administration was assisted by royal officials who served as advisors to the sultan.Key Words: History, Kingdom